2015
DOI: 10.5455/ajvs.177714
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study on Foot and Mouth Disease Virus in Beheira Governorate, Egypt during 2014

Abstract: Foot and mouth disease (FMD) is the most contagious disease of mammals and has a great potential for causing severe economic loss in susceptible cloven-hoofed animals. Egypt has a long history of occurrence of FMDV outbreaks, as the country is dependent on importation of live animals and meat from many countries all over the world. The present study was designed for detection, isolation and molecular characterization of FMDV circulating among different regions in Behaira governorate. Thirty-eight tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…The results of virus isolation on BHK21 cell line in this study revealed cell rounding, aggregation, clustering, and partial sheet detachments within 24-48hrs post infection. These results completely agreed with Ibrahim, et al (2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of virus isolation on BHK21 cell line in this study revealed cell rounding, aggregation, clustering, and partial sheet detachments within 24-48hrs post infection. These results completely agreed with Ibrahim, et al (2014).…”
Section: Discussionsupporting
confidence: 87%
“…The results of RT-PCR revealed FMD virus serotype O in the examined sample which has been responsible for many recent outbreaks in Egypt as reported by Ibrahim, et al (2014) and also by Aidaros, et al (2016) who found that the most prevalent serotype was (O) in Gharbia and Kaluabiagovernorates during 2014-2015. However, the involvement of other virus strains such as A and SAT2 were previously isolated in Egypt by El-Ashmawy, et al (2013), El-Bayoumy, et al (2014) and Ali, et al (2016).…”
Section: Discussionsupporting
confidence: 54%
“…Differentiating between these two categories of animals is important during serological surveys to detect evidence of infection in vaccinated animals [17]. Lower results of FMD detection were reported by El-Rhman et al [11] and a nearly similar result was reported by Salem et al [18], while higher results were reported by Ibrahim1 et al [19] and Zeedan et al [20] who used FMD-3ABC to distinguish FMDV-infected or carrier animals from vaccinated animals in Egypt.…”
Section: Discussionmentioning
confidence: 92%